A gestão do conhecimento esportivo: a experiência da biblioteca da Seme - Botelho, Maria Antonia [UNESP]; Monteiro, Ana Maria; Valls, Valéria (IBICT, 2007)
This study brings definitions related to knowledge, information services, information and knowledge management and lists the initiatives of sporting information management in Brazil. Describes the importance of the sports for the City of São Paulo in the context of public politics and budget resources, situates and describes the competencies of the Secretaria Municipal de Esportes, Lazer e Recreação of the City of São Paulo - Seme. Introduces, in detail, the Library: story, collection and relevant activities related to the process of knowledge management from Seme.

Este trabalho apresenta conceitos relativos a informação, conhecimento, serviços de informação, gestão da informação e do conhecimento e relaciona as iniciativas de gestão da informação esportiva no Brasil. Contextualiza a importância do esporte para a cidade de São Paulo, com destinação de recursos orçamentários e políticas públicas, situa e descreve as competências da Secretaria Municipal de Esportes, Lazer e Recreação da cidade de São Paulo (Seme). Apresenta detalhadamente a biblioteca: história, acervo e características de suporte ao processo de gestão do conhecimento da Seme.
The sporting knowledge management: an experience of Seme library
Keywords: Knowledge management; Sporting knowledge management; Sporting information system; Sporting information; Public information system; Gestão do conhecimento; Gestão do conhecimento desportivo; Sistema de informação esportiva; Serviço público de informação; Informação esportiva